(untitled) (Research, Society and Development, 2022)
Solanaceae as potential therapeutics that should be investigated, and several members of the Solanaceae family are used in the treatment of a series of clinical diseases such as respiratory, ophthalmological, Parkinson’s diseases, spasmodic conditions and as anti-inflammatory. The aim of this study is to present a systematic review protocol regarding extracts of the species Solanum Pseudoquina A. ST.-HIL (SOLANACEAE): prospection of the phytochemical and biological profile of the fruits. A bibliographic method was performed on the databases such as the Web of Science (WoS), Science Direct and Scopus databases, according to the established Ordinatio (MO) protocols. In parallel, based on the results, visualizations of the bibliometric network and mapping of results were made using the VOSviewer® software. It is considered through the studies presented that the results can be controlled, both the biological activities presented and those that are known as the scientific activities for these species.